Mediating and Moderating Factors Affecting Pro-environmental Decision-Making: A Spanish Study - Esther Cuadrado; Inmaculada Díaz-Carmona; Jorge Alcántara-Manzanares (Australian Journal of Environmental Education)
Because it is relevant to analyse the variables that may influence pro-environmental decision-making, the aim of this study was to analyse (a) the mediating role of perceived responsibility towards climate change (CC) in the relationship between scepticism towards CC and pro-environmental decision-making; and (b) the moderating role of implicit theories about CC (ITCC) in the relationship between responsibility and pro-environmental decision-making. For this purpose, 209 Spanish students (48.8% female, 43.1% male,and 8.1% preferring not to report their gender; mean age = 17.48, sd = 3.78) completed a questionnaire twice (two months apart) and subsequently (again, two months apart) indicated how many days they wanted to participate in a beach cleanup campaign. The results corroborate that (a) responsibility mediates the relationship between scepticism and pro-environmental decision-making, and (b) ITCC moderates the relationship between responsibility and pro-environmental decision-making. The study highlights the need to foster beliefs about the mitigation of CC and to promote reliable information in order to reduce scepticism towards CC, as well as feelings of responsibility towards CC in the field of Environmental Education.